PENGUAT KELAS D FREKUENSI TETAP ORDE 2 - Murtianta, Budihardja; Susilo, Deddy (Jurnal Edukasi Elektro, 2022)
ABSTRACT:The power amplifier determines the output power of the audio amplifier and in this part there will be heat dissipation which is proportional to the output power of the amplifier. To overcome the problem of the audio amplifier, a class D amplifier was designed. The amplifier designed in this paper is Power Amplifier Class D Fixed Frequency Second Order that uses a fixed frequency triangular signal generator and an order 2 low-pass filter. In this case, a power amplifier is designed for a subwoofer that has a frequency range of 20 Hz – 200 Hz because in the audio frequency range it requires relatively large power. The design of the power amplifier and its measurement using the Circuit Maker simulator. The amplifier can work to amplify signals with a maximum amplitude of 1 Vp and a frequency range of 20 Hz – 200 Hz. At a frequency of 20 Hz the shape of the signal is not as good as that of the 200 Hz frequency signal because it is far from the cut-off frequency of the low - pass filter, which is designed to be 250 Hz.ABSTRAK:Penguat daya menentukan besarnya daya keluaran penguat audio dan pada bagian ini akan terjadi disipasi panas yang sebanding dengan besar daya keluaran penguat. Untuk mengatasi permasalahan penguat audio tersebut dirancanglah penguat kelas D. Penguat yang di rancang pada tulisan ini adalah Penguat Kelas D Frekuensi Tetap Orde Dua yang menggunakan pembangkit sinyal segitiga frekuensi tetap dan tapis pelewat frekuensi rendah orde 2. Dalam hal ini dirancang penguat daya untuk subwoofer yang mempunyai jangkauan frekuensi 20 Hz – 200 Hz karena pada jangkauan frekuensi audio tersebut memerlukan daya relatif besar. Perancangan penguat daya dan pengukurannya menggunakan simulator Circuit Maker.  Penguat dapat bekerja memperkuat sinyal dengan amplitudo maksimum 1 Vp dan jangkauan frekuensi 20 Hz – 200 Hz. Pada frekuensi 20 Hz bentuk sinyal tidak sebaik  bentuk sinyal frekuensi 200 Hz karena jauh dari frekuensi penggal tapis pelewat frekuensi rendah yaitu dirancang 250 Hz.